New insights into the functional consequences of ephrin A3 mutations in non-small cell lung cancer - Whitsett, Timothy G.; Loftus, Joseph C.; Winkles, Jeffrey A.; Tran, Nhan L. (Translational Lung Cancer Research, 2012)
Lung cancer is the most commonly diagnosed cancer and the leading cause of cancer-related deaths worldwide (~1.4 million deaths in 2008) (1). Non-small cell lung cancer (NSCLC) is the most common lung cancer histological subtype (~85% of all lung cancers) and 50% of these tumors are adenocarcinomas.